Management of soil cover and its influence on phytosociology, physiology and fig production - Costa, Thiago da; Giacobbo, Clevison Luis; Galon, Leandro; Forte, Cesar Tiago; Damis, Richardson; Tironi, Siumar Pedro (Comunicata Scientiae, 2020)
The fig stands out as an important source of food for the human diet, especially minerals and fibers. Weeds are a major concern in the conduct of fig orchards. Therefore, the objective of this study was to evaluate the effect of management of vegetable cover of soil (CVS) on weed phytosociology, physiological characteristics and fig production. The experimental design was a randomized complete block design with four replications. The treatments consisted of six CVS managements: cover maintenance, weeding, lodging, mowing, application of herbicides diquat and glyphosate. For the constitution of the vegetal cover a consortium of three winter forage species, vetch and black oats sowed and the ryegrass remaining in the area of previous years were used. Thus, we evaluated the phytosociology of weeds present in the area, at two different times, assigning parameters related to frequency, density and abundance, which establish the species importance value index (IVI), besides the dry mass of the aerial part of the weeds. Physiological parameters and total fruit yield were evaluated at the end of the crop cycle. The different CVS management methods influenced the weed community, mainly in the diversity, density and dry mass of the aerial part. There is no interference in the physiological variables of the fig plants and in the total production of fig fruits. We highlight the maintenance of coverage and lodging as the most promising for the management of weeds found fig orchards.